Pregnancy Outcomes in Women With Mechanical Valve Prostheses Using Vitamin K Antagonist Therapy: The Experience of the Salam Centre for Cardiac Surgery in Sudan - Erba, Nicoletta; Gatti, Sofia; Hassan, Suha Abdelwahab Abdalla; Langer, Martin; Chatenoud, Liliane; Portella, Gina; Baiocchi, Raffaela (Frontiers in Pediatrics, 2022)
Pregnancy and childbirth on anticoagulants after mechanical heart valve replacement present a high risk of complications for both mother and baby. On top of pregnancy worsening the mother’s cardiac function, anticoagulant therapy itself is a crucial problem. A safe and effective anticoagulation regimen for both mother and fetus is not possible. The most effective drugs for preventing valve thrombosis are VKAs, whose dosage needs to be adjusted with frequent INR checks. Moreover, VKAs can have embryopathic and teratogenic action. Patients in follow-up and anticoagulant treatment at the Salam Centre for Cardiac Surgery in Sudan live spread out over a large area where transport to the Centre is generally difficult; pregnancy treatment has, therefore, been adapted to the limitations of reality. Pregnancy is discouraged and contraception and therapeutic abortion are recommended, but this guidance frequently goes unheeded. Here we describe maternal and fetal outcomes in 307 consecutive pregnancies recorded by staff at the oral anticoagulant clinic (OAC) from April 2017 to November 2021. Out of 307 pregnancies, there were 15 maternal deaths (4.9%), 24 thrombotic events (7.8%) and 22 major bleedings (7.2%). Fifty pregnancies (16.3%) were terminated by therapeutic abortion. Only 47.6% of pregnancies had good maternal and neonatal outcomes. Data clearly show that, due to the complexity of pregnancy in women with mechanical heart valves and the scarcity of tertiary healthcare services in the area where patients live, maternal mortality is at an unacceptable level and requires a structured, multi-disciplinary intervention.